Border parasites: schistosomiasis control among Uganda's fisherfolk - Parker, Melissa; Allen, Tim; Pearson, Georgina Pearson; Peach, Nichola; Flynn, Rachel; Rees, Nicholas (Informa UK Limited, 2012)
It is recognized that the control of schistosomisais in Uganda requires a focus on fisherfolk. Large numbers suffer from this water-borne parasitic disease; notably along the shores of lakes Albert and Victoria and along the River Nile. Since 2004, a policy has been adopted of providing drugs, free of charge, to all those at risk. The strategy has been reported to be successful, but closer investigation reveals serious problems. This paper draws upon long-term research undertaken at three locations in northwestern and southeastern Uganda. It highlights consequences of not engaging with the day to day realities of fisherfolk livelihoods; attributable, in part, to the fact that so many fisherfolk live and work in places located at the country's international borders, and to a related tendency to treat them as “feckless” and “ungovernable”. Endeavours to roll out treatment end up being haphazard, erratic and location-specific. In some places, concerted efforts have been made to treat fisherfolk; but there is no effective monitoring, and it is difficult to gauge what proportion have actually swallowed the tablets. In other places, fisherfolk are, in practice, largely ignored, or are actively harassed in ways that make treatment almost impossible. At all sites, the current reliance upon resident “community” drug distributors or staff based at static clinics and schools was found to be flawed.